Spectral Economies in Graham Swift’s Mothering Sunday: A Romance - Katarzyna Więckowska (Avant, 2017)
This article employs the concepts of spectres and haunting to analyse Graham Swift’s Mothering Sunday: A Romance (2016) as a commentary on (literary) history and its economy of spectres. Referring to Jacques Derrida’s notions of haunting, inheritance, and time, I focus on the spectres of literary modernism and the First World War to explore the ways in which Swift’s novella questions the canonical representation of modernism and revises the conventional means of writing about the past, memory, and history. The analysis of Mothering Sunday approaches the spectre as a figure of repressed otherness and a reminder of what has been excluded or silenced, so as to trace some of the ghosts that appear in the book and to underline its melancholic, spectral character. Situating Swift’s novella within the context of contemporary cultural criticism, I propose to see it as a sign of a larger cultural and critical turn, where spectres have been assimilated into the structure of the everyday and where the experience of haunting has become a major expression of the present condition.